KESENIAN & MATA PENCAHARIAN - Upaya Seniman Tradisional & Populer dalam Pemenuhan Nafkah - Kistanto, Nurdien Harry (Sabda: Jurnal Kajian Kebudayaan, 2012)
The traditional and popular artists have their fans, who are associated with levels of society and socio-economic conditions of the artists. Most artists appreciate the arts as a forum for the fulfillment of subsistence and some other artists treat art not merely as the main work in making a living, but as self-actualization and calling in life. Democratization, way of life & lifestyle have encouraged and accelerated development of new traditions in the arts; industrialization that took place since the early 1970s emphasized the political, policy and strategy choices of economy, trade and commercial business and service-based industries, which are very influential on the lives of the type, variety and artistic tastes. Deployment mode of art with industry and trade system applies to the popular performing arts, both departing from the tradition of Java and the growing management and modern technology, which supported the creation and innovation. With such developments, the traditional artists tend to be marginalized and subsistence efforts to meet with arts performances tend to be unprofitable, while popular artists through the art of business and trade industries tend to prosper. This research, among others, find authentic evidence from the field to confirm the truth of these allegations carefully, so that building theory and the concept of "the efforts of traditional and popular artists in the fulfillment of living life" is a field-based, not based on theory and concepts of the social and cultural sciences - called grand theory. In addition to utilizing the resources of media such as newspapers, magazines and internet websites, techniques of field observation and interviews, as well as in-depth interviews, which are commonly used in qualitative research, the mainstay of this research data collection.